Loop‐mediated isothermal amplification assay for rapid detection ofStreptococcus agalactiae(group B streptococcus) in vaginal swabs ‐ a proof of concept study. Issue 3 (March 2017) - McKenna, James Patrick; Cox, Ciara; Fairley, Derek John; Burke, Rachael; Shields, Michael D; Watt, Alison; Coyle, Peter Valentine
Abstract : Purpose. : Neonatal sepsis caused by Streptococcus agalactiae [group B streptococcus (GBS)] is a life‐threatening condition, which is preventable if colonized mothers are identified and given antibiotic prophylaxis during labour. Conventional culture is time consuming and unreliable, and many available non‐culture diagnostics are too complex to implement routinely at point of care. Loop‐mediated isothermal amplification (LAMP) is a method that, enables the rapid and specific detection of target nucleic acid sequences in clinical materials without the requirement for extensive sample preparation. Methodology. : A prototype LAMP assay targeting GBS sip gene is described. Results. : The assay was 100% specific for GBS, with a limit of detection of 14 genome copies per reaction. The clinical utility of the LAMP assay for rapid direct molecular detection of GBS was determined by testing a total of 157 vaginal swabs with minimal sample processing using a rapid lysis solution. Compared to a reference quantitative real‐time PCR assay, the direct LAMP protocol had a sensitivity and specificity of 95.4 and 100%, respectively, with positive and negative predictive values of 100 and 98.3%, respectively. Positive and negative likelihood ratios were infinity and 0.05, respectively. The direct LAMP method required a mean time of 45 min from the receipt of a swab to generation of a confirmed result, compared to 2 h 30 min for the reference quantitative real‐time PCR test. Conclusion. : The direct LAMP protocol described is easy to perform, facilitating rapid and accurate detection of GBS in vaginal swabs. This test has a potential for use at point of care.